Uncovering the Composition and Diversity of Pelagic Copepods in the Oligotrophic Blue Water of the South Pacific Subtropical Gyre - Medellín-Mora, Johanna; Escribano, Rubén; Corredor-Acosta, Andrea; Hidalgo, Pamela; Schneider, Wolfgang (Frontiers in Marine Science, 2021)
The subtropical gyres occupy ∼40% of the surface of the earth and are widely recognized as oligotrophic zones. Among them, the South Pacific subtropical gyre (SPSG) shows the lowest chlorophyll-a levels (0.02 - 0.04 μgL-1), the deepest nutricline (>200 m) and euphotic zone (~ 160 m), and the lowest rates of nitrogen fixation. The zooplankton community is poorly known in the SPSG and here we report a study focused on the composition and distribution of pelagic copepods within the gyre as to uncover the diversity and habitat conditions of this special community. For this, during the austral spring 2015 an oceanographic cruise was conducted across the eastern portion of the SPSG. Physical and chemical variables were measured in the upper 1000 m and zooplankton samples were collected by vertically stratified hauls using a multiple net sampler for five layers (0 - 800 m). Satellite data were also used to assess near-surface phytoplankton pigments and physical-dynamics conditions during the cruise. 121 species of copepods were identified belonging to 5 taxonomic orders, 24 families and 50 genera. Calanoida and Cyclopoida were the most frequent orders containing 57% and 38 % species, respectively, whereas Harpacticoida and Mormonilloida showed 2% of species each, and Siphonostomatoida with 1% of species. Vertical distribution of copepods revealed an ecological zonation linked to a strongly stratified water column, such that three different vertical habitats were defined: shallow (0-200m), intermediate (200-400m) and deep (400-800m). Both abundance and diversity of copepods were greater in the shallow habitat and strongly associated with water temperature, whereas copepods in the subsurface layers had to cope with low oxygen waters. presumably originated at the Chilean upwelling zone being transported offshore by mesoscale eddies. Also, the analysis of species composition revealed a marked dominance of small-sized copepods which may play a key role in nutrient recycling under an oligotrophic condition, as inferred from their mostly omnivorous feeding behavior. Our findings also suggested a potentially high endemism within the gyre, although basin-scale circulation and mesoscale eddies, travelling from the coastal upwelling zone and transporting plankton, can also influence the epipelagic fauna.